Impulse response analysis of coherent waveguide communication. Issue 1 (6th December 2017) - Kim, Yanghyo; Tang, Adrian; Cong, Jason; Chang, Mau-Chung Frank; Itoh, Tatsuo
Abstract : An impulse response method is carried out to analyze waveguide's information capacity within a coherent communication system. Such capability is typically estimated according to group delay variations (seconds/bandwidth/distance) after carrier-modulated data undergoes a dispersive medium. However, traditional group delay methods often ignore non-linear effects by assuming input data stream only occupies narrow bandwidth such that a propagation constant can be linearized centered at the carrier frequency. Such a constraint can be lifted with a proposed baseband equivalent impulse response method by using frequency domain convolution and multiplication. Once the impulse response in frequency domain is secured, its time domain counterpart can be calculated based on inverse Fourier transformation. Such analysis can fully reveal data pulse's broadening and gauge its inter-symbol interference by simply convolving input data with extracted impulse response, not limited to specific frequency range or type of waveguide.